A Parallel Belief Propagation Decoding Algorithm for Rate Compatible Modulation - Lu, Fang; Dong, Yan; Rao, Wengui (IEEE communications letters, 2017)
This letter proposes a parallel belief propagation algorithm for fast iterative decoding of rate compatible modulation. In this proposed algorithm, the processing at symbol node is partitioned into several low complexity sub-processors. All sub-processors have similar structures and work in parallel without cross connections among them. Numerical and simulation results show that proper partition results in significant reduction of the computational complexity without decoding performance degradation.